Cabbages and Kings: Posthumanistic Shakespeare on the Contemporary. Ukrainian Stage - Korneliuk, B.; Moskvitina, D.; Москвітіна, Дар'я Анатоліївна (My University, 2021)
The current Shakespearean stage in Ukraine is a patchwork of styles, play choices and artistic intentions. In the past three decades, post-Soviet Ukrainian theatre has developed its approach to Shakespeare, which can be characterized as “glocal”.
Moskvitina D. - https://orcid.org/0000-0001-9958-0962